2023
DOI: 10.3389/fimmu.2023.1223936
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spike antigen-specific B cell and antibody responses in pre-vaccination period COVID-19 convalescent males and females with or without post-covid condition

Marc-André Limoges,
Akouavi Julite Irmine Quenum,
Mohammad Mobarak Hussain Chowdhury
et al.

Abstract: BackgroundFollowing SARS-CoV-2 infection a significant proportion of convalescent individuals develop the post-COVID condition (PCC) that is characterized by wide spectrum of symptoms encompassing various organs. Even though the underlying pathophysiology of PCC is not known, detection of viral transcripts and antigens in tissues other than lungs raise the possibility that PCC may be a consequence of aberrant immune response to the viral antigens. To test this hypothesis, we evaluated B cell and antibody respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 104 publications
1
1
0
Order By: Relevance
“…Our findings broadly corroborate smaller community-based serological studies of early pandemic infections, which found evidence of stronger antibody responses in people with PCC compared to those with acute infections only (11,12), (13). The elevated, persistent anti-N response in people with PCC is suggestive of a stronger response to the acute infection, which could be driven by higher viral loads, a pro-inflammatory state and/or persistent viral antigens prompting the continued production of these antibodies (11).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings broadly corroborate smaller community-based serological studies of early pandemic infections, which found evidence of stronger antibody responses in people with PCC compared to those with acute infections only (11,12), (13). The elevated, persistent anti-N response in people with PCC is suggestive of a stronger response to the acute infection, which could be driven by higher viral loads, a pro-inflammatory state and/or persistent viral antigens prompting the continued production of these antibodies (11).…”
Section: Discussionsupporting
confidence: 86%
“…Two-year postinfection follow-up of 31 people with PCC and 31 acute-only controls found that markers of inflammation and anti-S and anti-N antibodies were elevated in people with PCC, but normalised to the levels of the acute-only group after 12-24 months (11); participants were infected prior to the availability of COVID-19 vaccines, but later post-vaccination antibody responses appeared to be similar between groups. Similarly, a cohort of people with mild SARS-CoV-2 infections who were unvaccinated at the time of infection found that anti-S levels were higher at three months in women with PCC compared to those with acute infections only, and that levels of anti-N antibody were similar between both groups (12). A further cohort of 51 community cases followed-up twice for 5-6 months post-infection found persistently elevated anti-S and anti-N antibody levels in people with greater post-infectious symptomatology (13).…”
Section: Introductionmentioning
confidence: 93%